Register-Bending in Québec Food Culture: translating nun’s farts and sunofabitch’s ears into something anyone would want to eat - Wheeler, Anne-Marie (Cuizine, 2015)
The food language of Québec’s cabanes à sucre represents a particularly salient example of what the English language has never successfully been able to communicate about québécois culture: how the politicized nature of French as it is spoken in Québec is played out in the collision and conflation of high and low registers, a tension between reverence and repulsion. This manifests itself in the realm of Québec’s food culture in the recent return of the nation’s high-end food purveyors and top chefs to their roots in maple-soaked deep-fried comfort foods, and the equally high and low register-bending, and thus largely untranslatable names, that accompany many dishes: des pets de soeurs, des oreilles de criss. This paper focuses on the work of celebrity chef Martin Picard, famous for his foie gras poutine and infamous for his squirrel sushi and tail-stuffed “Confederation Beaver,” arguing that his menu is essentially a form of food joual.